Evolutionary inferences of the terrestrial snail genus Gittenedouardia (Mollusca: Gastropoda: Cerastidae) with a comparative phylogeography aspect - Raphalo, Evelyn Mokgadi (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.